Hydrogen Sulfide Increases the Analgesic Effects of µ- and δ-Opioid Receptors during Neuropathic Pain: Pathways Implicated - Xue Bai; Gerard Batallé; Gianfranco Balboni; Olga Pol (MDPI AG, 2022)
Recent studies have revealed that hydrogen sulfide (H2S) increases the analgesic actions of the δ-opioid receptor (DOR) in inflammatory pain. However, the possible improvement of the analgesia of μ-opioid receptor (MOR) and DOR agonists during neuropathic pain, through pretreatment with two slow-releasing H2S donors-DADS (diallyl disulfide) and GYY4137 (morpholin-4-ium 4-methoxyphenyl(morpholino) phosphinodithioate dichloromethane complex)-is still unknown. In male C57BL/6J mice with neuropathic pain incited by chronic constriction of the sciatic nerve (CCI), we evaluated: (1) the influence of DADS (3.5 mg/kg) and GYY4137 (0.7 mg/kg) on the inhibition of the allodynia and hyperalgesia produced by the systemic or local administration of morphine (3 mg/kg or 65 µg) and UFP-512 (1 mg/kg or 12.5 µg); (2) the reversion of the antinociceptive actions of high doses of DADS (30 mg/kg) and GYY4137 (24 mg/kg) with MOR and DOR antagonists; and (3) the effects of H2S donors on oxidative stress, apoptotic responses, and MOR and DOR expression in the medial septum (MS) and dorsal root ganglia (DRG). The results revealed that both DADS and GYY4137 improved the antiallodynic effects of morphine and UFP-512, possibly by up-regulating MOR and DOR expression in DRG. The administration of MOR and DOR antagonists blocked the analgesic properties of DADS and GYY4137, revealing the feasible participation of the endogenous opioid system in H2S analgesic effects. Moreover, both H2S donors inhibited oxidative stress and apoptosis generated by CCI in the MS and/or DRG. This study suggests the co-treatment of H2S donors with MOR or DOR agonists as a potential therapy for neuropathic pain.